Comparisons of Mouse Mesenchymal Stem Cells in Primary Adherent Culture of Compact Bone Fragments and Whole Bone Marrow - Yiting Cai; Tianshu Liu; Fang Fang; Chengliang Xiong; Shiliang Shen (Stem Cells International)
The purification of mouse bone marrow mesenchymal stem cells (BMSCs) by using the standard method of whole bone marrow adherence to plastic still remains ineffective. An increasing number of studies have indicated compact bone as an alternative source of BMSCs. We isolated BMSCs from cultured compact bone fragments and investigated the proliferative capacity, surface immunophenotypes, and osteogenic and adipogenic differentiations of the cells after the first trypsinization. The fragment culture was based on the fact that BMSCs were assembled in compact bones. Thus, the procedure included flushing bone marrow out of bone cavity and culturing the fragments without any collagenase digestion. The cell yield from cultured fragments was slightly less than that from cultured bone marrow using the same bone quantity. However, the trypsinized cells from cultured fragments exhibited significantly higher proliferation and were accompanied with more CD90 and CD44 expressions and less CD45 expression. The osteogenic and adipogenic differentiation capacity of cells from cultured fragments were better than those of cells from bone marrow. The directly adherent culture of compact bone is suitable for mouse BMSC isolation, and more BMSCs with potentially improved proliferation capacity can be obtained in the primary culture.